Problem seeking : an architectural programming primer - Peña, William; Focke, John. (Boston, Massachusetts : Cahners Books International, Inc., 1977)
This book is a revision and expansion of problem seeking, a treatise on architectural programming, first published in 1969 and now out of print. We learned from problem seeking that the material was well received by professionals in various disciplines who were predisposed toward organized methods of inquiry.
Part One. An architecture programming primer -- The primer -- The search -- Programmers and designers -- Analysis and synthesis -- The separation -- The interface -- Five steps -- Procedure -- The whole problem -- Four considerations -- Framework -- Information index -- Organizing information -- Two-phase process -- Data clog -- Processing and discarding -- Abstract to the essence -- User on team -- Team -- Background information -- Decision making -- Communication -- Establish goals -- Collect and analyze facts -- Uncover and test concepts -- Cost estimate analysis -- State the problem -- Summary -- In a nutshell -- Part Two. The appendix -- A. Introduction -- B. Glossaries and examples -- C. Programming procedures -- D. Sophistication, situations and simplifications -- E. Useful techniques.
Includes bibliographical references and index.
Keywords: ARCHITECTURE -- DATA PROCESSING